Porous silicene and silicon graphenylene-like surfaces: a DFT study - Fabris, G. S. L. [UNESP]; Marana, N. L. [UNESP]; Longo, E.; Sambrano, J. R. [UNESP] (Springer, 2018)
Nanoporous single-layers surfaces derived from silicene, named porous silicene (PS) and silicenylene (SC) have been studied via periodic density functional theory with a modified B3LYP functional combined with an all-electron Gaussian basis set. The structural, elastic, electronic and vibrational properties of these nanoporous surfaces were simulated and analyzed. The results show that both PS and SC structures had a non-null band gap and a buckled structure such as pristine silicene, besides that they are more susceptible to longitudinal and transversal deformation than silicene. The large and well-defined porous diameter of PS and SC can bring new applications, such as gas separation, filtering and as anode material for lithium-ion batteries. These results are a challenge for the experimentalists to synthetize these new nanomaterials, comparing their properties with those described in this work.
Keywords: Nanoporous; Silicene; Graphene-like; Porous silicene; Modified functional; B3LYP